LOCATION OF MAGNETIC CONTACTS AND DEPTH ESTIMATES FOR THE MAGNETIC SOURCES FROM THE AEROMAGNETIC DATA OF MACEDONIA AND THRACE - Σταμπολίδης, Α.; Τσόκας, Γ. (Bulletin of the Geological Society of Greece, 2004)
In this work we present the processing that applied to digitised aeromagnetic data from Macedonia and Thrace. This processing was aiming the calculation of magnetic contacts and depths of burial of magnetic sources in the region of study. Three methods were applied for these calculations: the method of horizontal gradient, the method of analytical signal and the method of local wavenumber. All methods were successful in locating the deeper magnetic sources in basins and surface sources in regions with surface outcrops of the crystalline basement. Depending on the transformation of magnetic field we use as input for the methods of the horizontal gradient and analytical signal, we could calculate the minimum and maximum depths of burial for the magnetic contacts. The locations of magnetic contacts that were calculated for every method of analysis were combined in a map in order to help in the interpretation of proposed magnetic contacts